OP71 Mode of delivery and maternal sexual wellbeing: a longitudinal investigation of a UK-based cohort. (26th August 2022) - Martin, Florence; Madley-Dowd, Paul; Ahlqvist, Viktor; Bachmann, Egill Jónsson; Fraser, Abigail; Forbes, Harriet
Abstract : Background: The rates of both emergency and maternal request caesarean sections are increasing globally. Many factors are contributing to the rising rates and maternal outcomes are important to consider for care provision and decision-making. Qualitative evidence suggests that caesarean section is perceived to be protective of sexual function and thus enjoyment, however, this is evidenced by almost no long-term studies utilising quantitative methods. Emerging evidence suggests that caesarean section may be associated with sex-related pain postpartum but further longitudinal studies are needed. We investigated the relationship between mode of delivery and subsequent maternal sexual wellbeing, including sexual enjoyment, sexual frequency and sex-related pain. Methods: Mode of delivery was abstracted from obstretric records and sexual wellbeing measures were collected via self-report questionnaire using the Avon Longitudinal Study of Parents And Children (ALSPAC) cohort. Sexual enjoyment and frequency at four timepoints postpartum (between 33 months and 18 years), and two types of sex-related pain (pain in the vagina during sex and elsewhere after sex) at 11 years postpartum were used to investigate sexual wellbeing. Missing data were imputed using multiple imputation and ordinal logistic regression models for ordered categorical outcomes were adjusted for covariates maternal age at delivery, pre-pregnancy body mass index, socioeconomic position, parity, depression, and anxiety. Results: Caesarean section (vs vaginal delivery) was not associated with sexual enjoyment at any timepoint during follow-up (e.g., adjusted odds ratio [OR] 1.12, 95% confidence interval [95% CI] 0.98–1.28 at 33 months) or sexual frequency (OR 0.99, 95% CI 0.88–1.11 at 33 months). Caesarean section was associated with an increased odds of sex-related pain, at 11 years postpartum as compared with vaginal delivery in the adjusted models (OR 1.68, 95% CI 1.42–2.01 and OR 1.42, 95% CI 1.09–1.86, respectively). Discussion: These findings contradict perceptions of sexual wellbeing after caesarean section, as we found that caesarean section does not offer benefit over vaginal delivery in terms of long-term sexual enjoyment and that women who have delivered via caesarean section can suffer from sex-related pain that is not limited to abdominal scarring. Although these findings will not affect obstetric decision making during labour, it may aid in destigmatizing sex-related pain experienced by women having delivered via emergency caesarean section and open dialogue with their clinician regarding dyspareunia after delivery. For women considering a planned caesarean section in an uncomplicated pregnancy, evidence suggesting that caesarean section may not protect against sexual dysfunction may help inform the decision making process in the antenatal period.